2022
DOI: 10.1002/adma.202103168
|View full text |Cite
|
Sign up to set email alerts
|

Record‐High Superconductivity in Transition Metal Dichalcogenides Emerged in Compressed 2H‐TaS2

Abstract: Pressure has always been an effective method for uncovering novel phenomena and properties in condensed matter physics. Here, an electrical transport study is carried on 2H‐TaS2 up to ≈208 GPa, and an unexpected superconducting state (SC‐II) emerging around 86.1 GPa with an initial critical temperature (Tc) of 9.6 K is found. As pressure increases, the Tc enhances rapidly and reaches a maximum of 16.4 K at 157.4 GPa, which sets a new record for transition metal dichalcogenides (TMDs). The original superconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The key role of the oxidation state of transition metals in solids or molecular compounds is well established. The knowledge of this oxidation state is decisive to understanding the chemical behavior or the electronic and optical properties of such compounds as well as the mechanisms of reactions in which they are implied, for example, as catalyzing agents, gas sensors, or high- T c superconductors. An unambiguous signature of the oxidation state of transition metals can be found in X-ray photoelectron spectra (XPS). In copper oxides (CuO) and copper dihalides (CuX 2 , X = F, Cl, Br), the Cu 2p XPS spectra display a characteristic two-peak feature where the 2p 3/2 and 2p 1/2 main lines are both accompanied by a satellite band, at a relative distance of about 8–12 eV on the high binding energy (BE) side. The presence of satellite lines in the Cu 2p XPS spectra is a clear fingerprint of the Cu­(II) oxidation state, and their absence in Cu 2 O or metallic Cu compounds is the signature of the Cu­(I) oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…The key role of the oxidation state of transition metals in solids or molecular compounds is well established. The knowledge of this oxidation state is decisive to understanding the chemical behavior or the electronic and optical properties of such compounds as well as the mechanisms of reactions in which they are implied, for example, as catalyzing agents, gas sensors, or high- T c superconductors. An unambiguous signature of the oxidation state of transition metals can be found in X-ray photoelectron spectra (XPS). In copper oxides (CuO) and copper dihalides (CuX 2 , X = F, Cl, Br), the Cu 2p XPS spectra display a characteristic two-peak feature where the 2p 3/2 and 2p 1/2 main lines are both accompanied by a satellite band, at a relative distance of about 8–12 eV on the high binding energy (BE) side. The presence of satellite lines in the Cu 2p XPS spectra is a clear fingerprint of the Cu­(II) oxidation state, and their absence in Cu 2 O or metallic Cu compounds is the signature of the Cu­(I) oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, many theoretical and experimental studies have demonstrated that the CDW orders involved in the displacements are not only from the in-plane metallic atoms but also from the out-of-plane chalcogen atoms, , which may largely modulate the properties of adjacent components when fabricating them into VDWHs. Furthermore, it is well-known that the modulation of the CDW states through chemical or physical tuning tools commonly glues the superconducting properties, in that both of them originate from the instability of the Fermi surface and electron–phonon coupling (EPC).…”
mentioning
confidence: 99%
“…However, the studies of electronic properties induced by the CDW order, such as Mott insulating states and “better (or poor)” conductor behavior, and the relationship (e.g., coexisting, competing, or cooperating) between CDW and superconductivity within VDWHs are still limited. Furthermore, although a few successful cases have tuned the electrical-transport properties on 2D-limit layered materials, such as trilayer graphene in a diamond anvil cell, the wide-range applications of this technique to 2D VDWHs are still technically challenging.…”
mentioning
confidence: 99%
“…Until recent years, two-dimensional (2D)-layered materials have extensively been studied, attracting much attention owing to the variety of their potentials. Among those 2D-layered materials, tantalum disulfide (2H-TaS 2 ) is known to be a van der Waals conductor at room temperature but a superconductor at an extremely low temperature. , Here, thick 2D-layered TaS 2 has been partially oxidized in ultraviolet (UV) ozone (O 3 ) ambient at 250 °C to form a 12-nm-thin TaO X on conducting TaS 2 , so that the Ta-based insulating oxide/conductor (TaO X /2H-TaS 2 ) structure might be achieved in a self-assembled and deposition-free way, to operate as a platform of a memristor and a gate dielectric of a transistor as well. Tantalum oxide in the form of Ta 2 O 5–X or TaO X is well-known to be a high- k insulator but also able to function as a memristor when equipped with a proper electrode such as Cu. On one hand, for a transistor channel, β-Ga 2 O 3 is selected in consideration of its notable mechanical and semiconducting properties: temperature stability, large (∼4.8 eV) band gap-induced optical transparencies, high breakdown electric (E)-field, and minimum leakage current. Although thin β-Ga 2 O 3 is obtained from epitaxial growth on a sapphire substrate, , it could also be achieved by mechanical exfoliation after bulk crystal growth because monoclinic 3D β-Ga 2 O 3 has a largest interplanar distance in the (100)-orientation for cleavage.…”
mentioning
confidence: 99%
“…1−6 Among those 2D-layered materials, tantalum disulfide (2H-TaS 2 ) is known to be a van der Waals conductor at room temperature but a superconductor at an extremely low temperature. 7,8 Here, thick 2D-layered TaS 2 has been partially oxidized in ultraviolet (UV) ozone (O 3 ) ambient at 250 °C to form a 12-nm-thin TaO X on conducting TaS 2 , so that the Tabased insulating oxide/conductor (TaO X /2H-TaS 2 ) structure might be achieved in a self-assembled and deposition-free way, to operate as a platform of a memristor and a gate dielectric of a transistor as well. Tantalum oxide in the form of Ta 2 O 5−X or TaO X is well-known to be a high-k insulator but also able to function as a memristor when equipped with a proper electrode such as Cu.…”
mentioning
confidence: 99%